The Biogenesis, Biology, and Clinical Significance of Exosomal PD-L1 in Cancer - Tang, Yanyan; Zhang, Ping; Wang, Yumin; Wang, Jinpeng; Su, Min; Wang, Ying; Zhou, Lianqing; Zhou, Jumei; Xiong, Wei; Zeng, Zhaoyang; Zhou, Yujuan; Nie, Shaolin; et al. (Frontiers in Immunology, 2020)
The exosome serves as a trafficking vehicle for transport of programmed death-ligand 1 (PD-L1) into receptor cells. In tumor microenvironment, distant tumor cells can remotely attack activated T cells by exosomal PD-L1. Here, we summerize the biogenesis and transport process of exosomal PD-L1. Then, we focus on the cancer biology of exosomal PD-L1 in immunosuppression and the mechanism by which it inhibits T cells. Finally, we highlight the prospects of exosomal PD-L1 as a tumor biomarker and its significance in immunotherapy. In addition, we discuss the new challenges faced in researching and utilizing exosomal PD-L1. This review may shed light on the exosomal PD-L1 from the bench to the clinic.